2020
DOI: 10.3389/fneur.2020.00178
|View full text |Cite
|
Sign up to set email alerts
|

Playing Mahjong for 12 Weeks Improved Executive Function in Elderly People With Mild Cognitive Impairment: A Study of Implications for TBI-Induced Cognitive Deficits

Abstract: Background: Mild cognitive impairment (MCI) is common among elderly people. So far, effective treatment that can stabilize or reverse the cognitive decline associated with MCI is lacking. Recent studies suggest that playing mahjong may improve attention and memory in elderly people. However, its effect on executive function remains unknown.Methods: 56 elderly people (74.3 ± 4.3 years of age) with MCI from the First Social Welfare the First Nursing Home of Nanchong were randomized into mahjong and control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Non-modifiable risk factors include gender, age, ethnicity, heredity, and chronic diseases [ 13 , 14 , 15 ], whereas modifiable risk factors include physical activity, nutritional supplements, smoking, and alcohol abuse [ 16 , 17 , 18 ]. Additionally, recent studies have demonstrated that performing intellectual activities or games related to mental workload has a beneficial effect on cognitive function in older persons [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-modifiable risk factors include gender, age, ethnicity, heredity, and chronic diseases [ 13 , 14 , 15 ], whereas modifiable risk factors include physical activity, nutritional supplements, smoking, and alcohol abuse [ 16 , 17 , 18 ]. Additionally, recent studies have demonstrated that performing intellectual activities or games related to mental workload has a beneficial effect on cognitive function in older persons [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no cases in the literature reporting an improvement of executive functions after training AD patients with a game similar to the one employed in the present study. Recently, Zhang et al [16] reported that playing Mahjong for 12 weeks improved the executive function of elderly people with Mild Cognitive Impairment. Similarly, Kuo et al [17] found that multi-component cognitive training by playing card games for eight weeks improved executive functions in old adults, in contrast to an active control group.…”
Section: Discussionmentioning
confidence: 99%
“…The time required for the subject to complete the task will be recorded, less time suggesting better executive function. The test shows an acceptable level with respect to area under the curve (AUC = 0.835), sensitivity (84.6%), and specificity (66.7%) values among elderly people (> 65 years) with an education level <12 years ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Each correct answer is given 1 score, while incorrect answers or no answers are given 0 score. The cut-off value for the MoCA in the Chinese population is ≥26 ( 26 ).…”
Section: Methodsmentioning
confidence: 99%